2023
DOI: 10.1007/s13520-022-00165-y
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 global crisis and corporate social responsibility

Abstract: In order to gain greater insight into the nature of corporate social responsibility (CSR) during a time of crisis, the study examines the commitment of firms to continue to engage in CSR activity despite financial pressures to divert their slack resources elsewhere. The setting of the study is CSR activity during the perhaps unprecedented global crisis associated with the COVID-19 pandemic. Based on a qualitative research method approach, both a variety of media sources and the relevant academic literature are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 72 publications
0
4
0
1
Order By: Relevance
“…Previous research has analysed the difference between family management and family ownership (Block and Wagner, 2014a, b) but not in the context of slack resources usage. Practically, family owners shall have strong power to influence family managers to use absorbed slack for CSR activities as CSR activities are very much needed in the pandemic and post-pandemic era (Schwartz and Kay, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has analysed the difference between family management and family ownership (Block and Wagner, 2014a, b) but not in the context of slack resources usage. Practically, family owners shall have strong power to influence family managers to use absorbed slack for CSR activities as CSR activities are very much needed in the pandemic and post-pandemic era (Schwartz and Kay, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that crisis-related brand messages were more effective for consumers with lower social connection during the pandemic (Garcia-Collart, 2023). The pandemic has become a significant social cause in brand messages, influencing consumers’ perception of CSR communication (Schwartz and Kay, 2023). Early messages focused on promoting public health and safety, while later ones aimed to uplift and offer support (Jordan, 2021).…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Untuk menentukan format laporan keberlanjutan yang tepat bagi UMKM memerlukan pertimbangan dari perspektif pemangku kepentingan dalam penerapan akuntansi keberlanjutan (Schwartz & Kay, 2023). Penelitian ini mengkaji peran dua pemangku kepentingan, National Center of Corporate Reporting (NCCR) dan UMKM.…”
Section: Hasil Dan Pembahasan Pemahaman Umkm Terhadap Laporan Keberla...unclassified